The GAAR of the ATAD: implications on taxpayer rights and access to the fundamental freedoms associated with lack of legal certainty - Rozenšteina, Madlēna Melinda (Riga Graduate School of Law, 2020)
This contribution is a body of doctrinal research, which endeavours to establish whether the GAAR can be effective in both discouraging illegitimate tax avoidance and upholding the rule of law sufficiently to not undermine taxpayer rights and the integrity of the internal market. In answering this research question the contribution relies predominantly on the analysis of the principles established in the CJEU case law.The contribution outlines the challenges associated with interpreting the GAAR based on the abuse of law doctrine established in the CJEU, and highlights the issues that may lead to inconsistent interpretation of the tests for identifying abuse. The contribution finds that insufficiencies in the interpretation of the provisions contained in the GAAR and the minimum standard nature of the ATAD are likely to provide a lack of certainty that, in turn, impacts the taxpayer's ability to clearly anticipate the legitimacy of potential tax planning strategies. Lack of certainty also appears to have the potential to affect the consistency with which the GAAR may be interpreted across the individual Member States, potentially creating asymmetry, which could lead to unequal access to the Fundamental Freedoms and thus distort the internal market. This contribution concludes that, in order to uphold the rule of law within the EU legal system and protect the internal market, the EU must define an upper limit outlining the extent to which the Fundamental Freedoms may be restricted when applying the GAAR. New CJEU case law will have to serve as a tool to mitigate the effects of asymmetry in the national application of the GAAR. Accordingly, while the contribution allows that the initial application of the GAAR may be inconsistent, further developments in CJEU interpretations of the GAAR should provide a more uniform interpretation of the GAAR.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Research Subject Categories::LAW/JURISPRUDENCE::Financial law